Political and legal views of Zoroaster and their importance in the history of political and legal doctrines of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
The article devoted to analyzes of the domestic and foreign scientists works about the origin of the prophet Zarathustra and the author offers his own scientific opinion on this matter. Exploring the personality of Zarathustra as the first prophet who spread the idea of monotheism, the author examines his views and political and legal ideas. On this regard, he refers to the data of the history about the study of the Avesta – the holy book of Zoroastrianism, using scientific research on this field. The article deals with the political views of Zarathustra about government, state, social management through its division into certain class of society which are contained in the ghats of Avesta. In conclusion, the author makes a conclusion about the significance and the role of political and legal views of Zoroaster in the history of political and legal doctrines of Kazakhstan.Key words: political and legal ideas, Zoroaster, Avesta, ghats.